Uremic Leontiasis Ossea due to Resistant Secondary Hyperparathyroidism - Kubra Tuna, MD; Olesya Ilkun, MD, PhD; Peter T. Dziegielewski, MD; Anu Sharma, MD (AACE Clinical Case Reports)
Background/Objective: Severe progressive overgrowth of the facial bones known as uremic leontiasis ossea (ULO) is a rare complication of resistant hyperparathyroidism in end-stage renal disease (ESRD). The objective of this report is to describe the presentation and treatment of ULO. Case Report: A 48-year-old woman with a history of hypertension, coronary artery disease, and ESRD on hemodialysis presented with severe secondary hyperparathyroidism and calciphylaxis. She had significant changes to her face in the last 3 months leading to oropharyngeal dysphagia and difficulty articulating. Physical examination revealed bony overgrowth in her upper jaw and hard palate, widely spaced teeth, and calcinosis cutis. Her parathyroid hormone (PTH), calcium, and phosphorus levels were 5066 pg/mL (normal range, 12-88 pg/mL); 10.0 mg/dL (8.4-10.2 mg/dL); and 5.4 mg/dL (2.7-4.5 mg/dL); respectively. Using a multidisciplinary approach, she successfully underwent a 3.5-gland parathyroidectomy (immediate postoperative PTH level, 600 pg/mL). She was discharged without complication. Pathology showed hypercellular parathyroid glands with reactive changes. Discussion: ULO, the most severe form of renal osteodystrophy, results in hypertrophy of the craniofacial skeleton. It carries the risk of significant comorbidities due to cranial nerve compression, respiratory compromise, dysarthria, and dysphagia. Conclusion: With prolonged, uncontrolled PTH stimulation in ESRD, significant facial disfiguration with disabilities can occur. It is of utmost importance to adhere to guideline-specified PTH targets in persons with ESRD to prevent patient harm from permanent physical deformities.